SUSTAINABLE TRANSPORTATION IN SOUTHEAST ASIAN COUNTRIES: IMPLEMENTATION OF GREEN TRANSPORT - Maudina, Nafrah; Purnomo, Eko Priyo (UI Scholars Hub, 2023)
Metropolitan cities face escalating reliance on private transportation, exacerbating traffic congestion and air pollution. To address these issues, promoting eco-friendly alternatives like Mass Rapid Transit (MRT), Bus Rapid Transit (BRT), and electric vehicles is crucial. This study aims to explore the integration of green transportation to achieve Sustainable Development Goals (SDGs), utilizing bibliographical analysis with VOSviewers tools. Scopus-indexed articles (2010-2022) were scrutinized using keywords: